2016
DOI: 10.4103/0976-237x.177112
|View full text |Cite
|
Sign up to set email alerts
|

Can bone marrow aspirate concentrate change the mineralization pattern of the anterior maxilla treated with xenografts? A preliminary study

Abstract: Objective:To evaluate bony reconstruction of the atrophic anterior maxilla using particulate grafts with or without autologous bone marrow aspirate concentrate (BMAC).Materials and Methods:Eight patients with atrophy of the anterior maxilla due to teeth loss were selected and split into groups according to the type of material used: Control Group (CG) (n = 4) - particulate xenograft only and Test Group (TG) (n = 4) - a combination of particulate xenograft and BMAC. Both groups received a collagen membrane to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 16 publications
4
20
0
2
Order By: Relevance
“…After assessment of the full papers, a further 56 records were excluded. Therefore, a total of 18 publications corresponding to 16 original studies were included for qualitative analysis. One of the included studies reported follow‐up data from a previously published study , whereas another one was a correction of a previous report .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After assessment of the full papers, a further 56 records were excluded. Therefore, a total of 18 publications corresponding to 16 original studies were included for qualitative analysis. One of the included studies reported follow‐up data from a previously published study , whereas another one was a correction of a previous report .…”
Section: Resultsmentioning
confidence: 99%
“…There was a total of 11 randomized controlled trials (RCTs) and 5 non‐randomized controlled original trials included for qualitative analysis. All RCTs incorporated a parallel design, whereas CCTs included reports with either a parallel or a “split mouth” design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations